I Promessi Sposi di Alessandro Manzoni: un libro bellissimo e attualissimo - Umberto Melotti (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The 150th anniversary of Alessandro Manzoni’s death was celebrated beyond all expectations. The President of the Republic himself wished to commemorate it with a statement emphasising the beauty and relevance of The Betrothed, a novel that should be read in adulthood, when one can most appreciate its great richness. There is, however, one difficulty: his writing suffers the effects of time. More than 200 years have passed since it was first written, a little less since its first published version and more than 180 since its definitive version, and language, like any living thing, evolves, all the more so in a period marked by so many important transformations. This is why I have participated in the Manzoni celebrations by publishing the full transcription in modern Italian. But, as a sociologist, in this work, which lasted more than five years, I first of all grasped the validity of that novel also in its sociological aspects.